MANAJEMEN SUMBER DAYA MANUSIA BERBASIS GOOD UNIVERSITY GOVERNANCE (GUG) PADA STKIP BINA BANGSA GETSEMPENA - Rossiana Ginting; Cut Zahri Harun; Nasir Usman (Jurnal Visipena, 2020)
The implementation of Good University Governance (GUG) in a university can be seen from human resource management. The better the management of human resources in a university means showing that the college will be more superior. This is what motivates the researcher to research the resource management of a university, namely STKIP Bina Bangsa Getsempena. The aim of this research is to find out whether the college applies the principles of Good University Governance (GUG) in human resource management. This study uses a descriptive method with a qualitative approach. The data collection techniques used were interviews, observation and documentation study. The research subjects were the Head of the Academic Administration Bureau, the Deputy Chair for Academic Affairs and the Human Resource Department of the Getsempena Education Foundation. The data were analyzed using reduction techniques, presentation and conclusion drawing. The results showed: (1) Recruitment and selection at STKIP Bina Bangsa Getsempena using the principles of Good University Governance (GUG), namely the principles of transparency and accountability; (2) Placement at STKIP Bina Bangsa Getsempena uses the principles of Good University Governance (GUG), namely the principle of accountability; (3) Training and preparation of career paths at STKIP Bina Bangsa Getsempena using the principles of Good University Governance (GUG), namely the principles of accountability, responsibility, independence and fairness; (4) Enforcement of discipline and giving awards to educators and educational staff at STKIP Bina Bangsa Getsempena using the principle of fairness; (5) Termination at STKIP Bina Bangsa Getsempena shall use the principle of independence and fairness. Barriers to human resource management are the replacement of human resources on the grounds of resignation. An Educator and Education Personnel who resign will interfere with the structural performance of higher education. Abstrak Penerapan Good University Governance (GUG) pada sebuah perguruan tinggi dapat dilihat dari manajemen sumber daya manusia. Semakin baik manajemen sumber daya manusia dalam sebuah perguruan tinggi berarti menujukkan bahwa perguruan tinggi tersebut akan semakin unggul. Hal ini adalah yang melatarbelakangi Peneliti untuk meneliti manajemen sumber daya sebuah Perguruan Tinggi yaitu STKIP Bina Bangsa Getsempena.Tujuan penelitian untuk mengetahui apakah perguruan tinggi tersebut menerapkan prinsip-prinsip Good University Governance (GUG) dalam manajemen sumber daya manusia. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dengan metode wawancara, observasi dan studi dokumentasi.Subjek penelitian adalah Kepala Biro Administrasi Akademik, Wakil Ketua Bidang Akademik dan Human Resource Department Yayasan Pendidikan Getsempena.Data dianalisis dengan teknik reduksi, penyajian dan penarikan kesimpulan. Hasil penelitian menunjukkan: (1) Rekrutmen dan seleksi pada STKIP Bina Bangsa Getsempena menggunakan prinsip Good University Governance (GUG) yaitu prinsip transparansi dan akuntabilitas; (2) Penempatan pada STKIP Bina Bangsa Getsempena menggunakan prinsip Good University Governance (GUG) yaitu prinsip akuntabilitas; (3) Pelatihan dan penyusunan jenjang karier pada STKIP Bina Bangsa Getsempena menggunakan prinsip Good University Governance (GUG) yaitu prinsip akuntabilitas, pertanggungjawaban, independensi, dan kewajaran; (4) Penegakan disiplin dan pemberian penghargaan kepada tenaga pendidik dan tenaga kependidikan pada STKIP Bina Bangsa Getsempena menggunakan prinsip kewajaran; dan (5) Pemberhentian pada STKIP Bina Bangsa Getsempena menggunakan prinsip independen dan kewajaran. Hambatan dalam manajemen sumber daya manusia yaitu pergantian sumber daya manusia dengan alasan pengunduran diri. Seorang Tenaga Pendidik dan Tenaga Kependidikan yang mengundurkan diri akanmengganggu kinerja struktural perguruan tinggi.